2021
DOI: 10.3389/fphys.2021.616985
|View full text |Cite
|
Sign up to set email alerts
|

3D-FV-FE Aeroacoustic Larynx Model for Investigation of Functional Based Voice Disorders

Abstract: For the clinical analysis of underlying mechanisms of voice disorders, we developed a numerical aeroacoustic larynx model, called simVoice, that mimics commonly observed functional laryngeal disorders as glottal insufficiency and vibrational left-right asymmetries. The model is a combination of the Finite Volume (FV) CFD solver Star-CCM+ and the Finite Element (FE) aeroacoustic solver CFS++. simVoice models turbulence using Large Eddy Simulations (LES) and the acoustic wave propagation with the perturbed conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 112 publications
(276 reference statements)
5
42
0
Order By: Relevance
“…A promising approach for a screening tool fulfilling these requirements could be based on bioacoustic signals such as speech sounds or cough sounds (Brown et al, 2020;Hecker et al, 2021;. Several studies have reported acoustic peculiarities in the speech of patients who have diseases associated with symptoms affecting anatomical correlates of speech production, such as bronchial asthma (Balamurali et al, 2020;Dogan et al, 2007) or vocal cord disorders (Falk et al, 2021;Jesus et al, 2015;Petrović-Lazić et al, 2011). Differences in various acoustic parameters were also found in recent studies comparing speech samples of COVID-19 positive and COVID-19 negative individuals (Asiaee et al, 2020;Bartl-Pokorny et al, 2021).…”
Section: Disease Detection Based On Bioacoustic Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising approach for a screening tool fulfilling these requirements could be based on bioacoustic signals such as speech sounds or cough sounds (Brown et al, 2020;Hecker et al, 2021;. Several studies have reported acoustic peculiarities in the speech of patients who have diseases associated with symptoms affecting anatomical correlates of speech production, such as bronchial asthma (Balamurali et al, 2020;Dogan et al, 2007) or vocal cord disorders (Falk et al, 2021;Jesus et al, 2015;Petrović-Lazić et al, 2011). Differences in various acoustic parameters were also found in recent studies comparing speech samples of COVID-19 positive and COVID-19 negative individuals (Asiaee et al, 2020;Bartl-Pokorny et al, 2021).…”
Section: Disease Detection Based On Bioacoustic Signalsmentioning
confidence: 99%
“…Although research on the automatic detection of diseases based on speech is rapidly expanding, it faces a number of challenges in terms of algorithm generalisability and potential application in real-world scenarios. These challenges include gender and age distribution, the presence of different mother tongues, dialects, sociolects, or cognitive aspects such as individual speech-language and reading competence that may affect various acoustic parameters (Alves et al, 2015;Goyal et al, 2021;Nagumo et al, 2020;Procter & Joshi, 2020;Rojas et al, 2020;Sun, 2020;Taylor et al, 2020). Studies on COVID-19 face additional challenges related to the fact that COVID-19 is a relatively new and not yet well understood disease with a wide range of symptoms and divergent symptom severity (Hu et al, 2020;Tu et al, 2020).…”
Section: Disease Detection Based On Bioacoustic Signalsmentioning
confidence: 99%
“…The detailed description of the model with focus on the numerical efficiency is provided in [37], whereas a thorough description of the CFD incompressible flow simulation can be found in [31] and [30]. Furthermore, an extensive source term analysis for a validated synthetic setup is provided in [36] and the application to typical vocal cord dysfunctions is presented in [7].…”
Section: Self Excited (Fsi) Pde-based Modelsmentioning
confidence: 99%
“…Radiation to an open space was not considered in this study, similarly as in other studies [19,43,60,62,83,86,87]. The PML layer of elements used in some models [24,63] could not be applied here because the PML layer is designated for acoustical elements rather than the elements for fluid flow simulations.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Many authors created new models of phonation with a prescribed movement of the VF and the acoustic analogy or APE. They showed that the dominant acoustic source is the sound generated by the flow through the glottis [9,34,58,85] and the prescribed (driven kinematic) VF movement is reasonable simplification resulting in lower computational costs [24,50,51,63,87]. Yet Alipour et al upgraded their model [2,4] with the self-oscillating VFs and found that the distributions along the centerline axis in this model were similar as in [19,27,52,69] and the presented formants of the vowels [a:] and [i:] were in good correspondence to those observed in humans.…”
Section: Introductionmentioning
confidence: 99%